Introduction to Places of Worship of Religious People in Indonesia Augmented Reality Based As Learning Media for Early childhood - Hadi, Miftakhul; Astutik, Ika Ratna Indra; Rosid, Mochamad Alfan; Fitrani, Arif Senja (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to introduce an innovative method for religious learning among early childhood in Indonesia by leveraging augmented reality (AR) technology. The research utilizes marker-based tracking, which does not require high-performance Android devices, to create a seamless interaction between virtual religious objects and the real world. The multimedia development lifecycle method is employed in application development, successfully operating on Android devices with versions 7.0 and above. The results demonstrate relatively good marker quality even when printed at A4 and F4 sizes. This research underscores the potential of AR technology as a powerful tool for instilling religious knowledge and habits in young children, offering a promising avenue for future educational interventions. Highlights: AR Enhances Early Religious Education: Augmented reality technology offers an engaging and effective platform for imparting religious knowledge to young children. Marker-Based Simplicity: The use of marker-based tracking simplifies AR implementation, making it accessible even on lower-end Android devices. Potential for Future Interventions: This research highlights the promising potential of AR in early childhood education, paving the way for innovative pedagogical approaches. Keywords: Augmented Reality, Early Childhood Education, Religious Learning, Marker-Based, Tracking, Multimedia Development